If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 + x + 1 = (x + 5) + (4x + -1) + (4x + 3) Reorder the terms: -4 + 1 + 4x + x = (x + 5) + (4x + -1) + (4x + 3) Combine like terms: -4 + 1 = -3 -3 + 4x + x = (x + 5) + (4x + -1) + (4x + 3) Combine like terms: 4x + x = 5x -3 + 5x = (x + 5) + (4x + -1) + (4x + 3) Reorder the terms: -3 + 5x = (5 + x) + (4x + -1) + (4x + 3) Remove parenthesis around (5 + x) -3 + 5x = 5 + x + (4x + -1) + (4x + 3) Reorder the terms: -3 + 5x = 5 + x + (-1 + 4x) + (4x + 3) Remove parenthesis around (-1 + 4x) -3 + 5x = 5 + x + -1 + 4x + (4x + 3) Reorder the terms: -3 + 5x = 5 + x + -1 + 4x + (3 + 4x) Remove parenthesis around (3 + 4x) -3 + 5x = 5 + x + -1 + 4x + 3 + 4x Reorder the terms: -3 + 5x = 5 + -1 + 3 + x + 4x + 4x Combine like terms: 5 + -1 = 4 -3 + 5x = 4 + 3 + x + 4x + 4x Combine like terms: 4 + 3 = 7 -3 + 5x = 7 + x + 4x + 4x Combine like terms: x + 4x = 5x -3 + 5x = 7 + 5x + 4x Combine like terms: 5x + 4x = 9x -3 + 5x = 7 + 9x Solving -3 + 5x = 7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 5x + -9x = 7 + 9x + -9x Combine like terms: 5x + -9x = -4x -3 + -4x = 7 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -4x = 7 + 0 -3 + -4x = 7 Add '3' to each side of the equation. -3 + 3 + -4x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = 7 + 3 -4x = 7 + 3 Combine like terms: 7 + 3 = 10 -4x = 10 Divide each side by '-4'. x = -2.5 Simplifying x = -2.5
| 80-3g=5t-8 | | B-125=200 | | 80=200-40x | | 81+62+x=180 | | 1/4(60+16s)=15+4 | | 7+8z= | | 5+42x=28x+23 | | 50=30+n | | 6(3+4x)-8=130 | | 16x^2-3x-10=0 | | 9+(4t)=1(2t) | | .6=5/x | | 129+116+130+120+135+125+y=900 | | 5/x=.6 | | 20+n=30 | | -2/3×9 | | 6(x-3)-4x=20 | | 12-7y-6y=64 | | (x/5)-10=x=2 | | -3(2x+7)+(-3x+6)-8(1-2x)-x-3=0 | | 14.95+0.13m=-15.00+0.39 | | 117+100+105+115+x=540 | | 3x+23-7x+14=13x+28+25x+72 | | 6x-(5x-3)=6 | | 1/8(16m-8)-17= | | 7/b-36=a/72 | | 3x+1y=31.5 | | 120+85+53+x=360 | | Inx=-1 | | a-25=5 | | .25(60-y)+.10(y)=9.45 | | X^2+50-400=0 |